2007
DOI: 10.1212/01.wnl.0000256698.69121.45
|View full text |Cite
|
Sign up to set email alerts
|

IV immunoglobulin in patients with myasthenia gravis

Abstract: This study provides level 1 evidence for the effectiveness of IV immunoglobulin in patients with worsening weakness due to myasthenia gravis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
177
1
10

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(196 citation statements)
references
References 19 publications
6
177
1
10
Order By: Relevance
“…PLEX effectively improves strength in most patients with severe MG [46,47]. IVIg is widely used for patients with exacerbating MG. Randomized controlled trials that show efficacy similar to PLEX [46], and a double-blind, placebo-controlled trial in patients with MG with worsening weakness [48], support its use in the clinic. Randomized controlled trials comparing IVIg with plasmapheresis have shown no significant differences between the two in treatment of an acute MG exacerbation [49], but PLEX may have a faster onset of action and is the treatment of choice in MG crisis.…”
Section: Present Management Of Autoimmune Mgmentioning
confidence: 84%
“…PLEX effectively improves strength in most patients with severe MG [46,47]. IVIg is widely used for patients with exacerbating MG. Randomized controlled trials that show efficacy similar to PLEX [46], and a double-blind, placebo-controlled trial in patients with MG with worsening weakness [48], support its use in the clinic. Randomized controlled trials comparing IVIg with plasmapheresis have shown no significant differences between the two in treatment of an acute MG exacerbation [49], but PLEX may have a faster onset of action and is the treatment of choice in MG crisis.…”
Section: Present Management Of Autoimmune Mgmentioning
confidence: 84%
“…A randomized placebo controlled trial reported the efficacy of intravenous immunoglobulins in worsening Myasthenia Gravis patients; the primary outcome was the Quantitative MG Score (QMG) assessed at baseline and at 14 and 28 days. Improvement was statistically significant at 14 days while the Quantitative MG Score at 28 days failed to reach statistic significance (Zinman et al, 2007).…”
Section: High Dose Intravenous Immunoglobulinsmentioning
confidence: 82%
“…Moreover, the controlled study reported by Zinman and coworkers (Zinman et al, 2007) included patients with muscle specific tyrosine kinase-associated Myasthenia Gravis; even though the results were not given for each antibody subgroup, the overall results indicate improvement also in patients without anti-acetylcholine receptor antibodies. This is particularly important for muscle specific tyrosine kinase-positive Myasthenia Gravis in case of respiratory insufficiency, when TPE is not available or not feasible.…”
Section: High Dose Intravenous Immunoglobulinsmentioning
confidence: 99%
“…The usefulness of IVIG is best proved for GBS, in which several RCTs find IVIG and plasmapheresis to be equally efficacious [368]. IVIG is also beneficial in the treatment of myasthenic crisis, an approach that is supported by a single randomized trial [369]. Results from randomized trials comparing the efficacy of IVIG and plasmapheresis in myasthenia exacerbations are equivocal [288].…”
Section: Intravenous Immunoglobulinmentioning
confidence: 99%